Abnormal serum microRNA profiles in tuberous sclerosis are normalized during treatment with everolimus: possible clinical implications. Issue 1 (December 2016) - Trelinska, Joanna; Fendler, Wojciech; Dachowska, Iwona; Kotulska, Katarzyna; Jozwiak, Sergiusz; Antosik, Karolina; Gnys, Piotr; Borowiec, Maciej; Mlynarski, Wojciech
Abstract Background Tuberous sclerosis (TSC) is a monogenic disease resulting from defects of theTSC1 orTSC2 genes, which encode the proteins forming hamartin-tuberin tumor suppressor complex, the mammalian target of rapamycin complex (mTOR). The mTOR pathway is constitutively activated in response to tuberin or hamartin defects. The mTOR pathway is also regulated by a multitude of epigenetic mechanisms, one of which is regulation by microRNA (miRNA) inhibition. This leads us to hypothesize that organ-level abnormalities of miRNA expression patterns are widespread in TSC. The aim of the study was to evaluate the serum profiles of miRNAs in patients with TSC and subependymal giant cell astrocytoma (SEGA) treated with mTOR inhibitor (everolimus). Methods Serum microRNA profiling was performed in 10 TSC-patients before and three months after everolimus treatment, as well as in 10 sex- and age-matched healthy controls. MicroRNAs were profiled using qPCR panels (Exiqon). Results Of 752 tested miRNAs, 11 showed statistically significant dysregulation in patients with TSC in comparison to controls. The following miRNAs were downregulated in TSC: miR-142-3p, miR-199a-5p, miR-142-5p and miR-136-5p; while miR-130a-3p, miR-378a-3p, miR-130b-3p, miR-192-5p, miR-25-3p, miR-215-5p and miR-222-3p were upregulated in TSC in comparison to the control group. After three months of everolimus treatment, mean dose 5.1 (2.6-9.7) mg/m2, seven miRNAs reached expression levels similar to healthy controls, with miR-142-3p and miR-136 showed significant increase over baseline levels in TSC patients. Moreover, miR-222-3p normalization due to treatment differed between patients with mutation inTSC1 andTSC2 gene. Conclusions Activation of the mTOR pathway in TSC patients alters serum miRNA levels, which may be partially reversed by an mTOR inhibitor. This indicates the involvement of miRNA dysregulation in the pathogenesis of TSC, linking miRNA profiles with treatment efficiency.